Gh̳ana sessions with Mattew Caruana in the Manuel Casha Maltese folklore music project. - Caruana, Mattew (2002)
Folkloric recording.
Gh̳ana (pronounced anah) is the Maltese term for folksong or sung poetry, within gh̳ana are a number of forms, amongst them are spiritu pront, which means quick thought and is the most well known, extemporised form of gh̳ana.
Recorded on 24 January 2002 in Albion, Victoria.
Digital master available
Songs performed in Maltese.
Summary not yet available.
Keywords: Folk songs, Maltese; Poetry, Maltese; Maltese Australians -- Music